What Is in the Field for Genetics and Epigenetics of Diabetic Neuropathy: The Role of MicroRNAs - V. Spallone; C. Ciccacci; A. Latini; P. Borgiani (Journal of Diabetes Research)
Despite the high prevalence of diabetic neuropathy, its early start, and its impact on quality of life and mortality, unresolved clinical issues persist in the field regarding its screening implementation, the understanding of its mechanisms, and the search for valid biomarkers, as well as disease-modifying treatment. Genetics may address these needs by providing genetic biomarkers of susceptibility, giving insights into pathogenesis, and shedding light on how to select possible responders to treatment. After a brief summary of recent studies on the genetics of diabetic neuropathy, the current review focused mainly on microRNAs (miRNAs), including the authors’ results in this field. It summarized the findings of animal and human studies that associate miRNAs with diabetic neuropathy and explored the possible pathogenetic meanings of these associations, in particular regarding miR-128a, miR-155a, and miR-499a, as well as their application for diabetic neuropathy screening. Moreover, from a genetic perspective, it examined new findings of polymorphisms of miRNA genes in diabetic neuropathy. It considered in more depth the pathogenetic implications for diabetic neuropathy of the polymorphism of MIR499A and the related changes in the downstream action of miR-499a, showing how epigenetic and genetic studies may provide insight into pathogenetic mechanisms like mitochondrial dysfunction. Finally, the concept and the data of genotype-phenotype association for polymorphism of miRNA genes were described. In conclusion, although at a very preliminary stage, the findings linking the genetics and epigenetics of miRNAs might contribute to the identification of exploratory risk biomarkers, a comprehensive definition of susceptibility to specific pathogenetic mechanisms, and the development of mechanism-based treatment of diabetic neuropathy, thus addressing the goals of genetic studies.